Avaliação histológica do capeamento pulpar direto com sericina de seda em ratos: um estudo preliminar - Hartmann, Giovani Ceron (2018)
This study analyzed sericin as a potential biomaterial in contact with dentin pulp, histologically comparing its response to direct pulp capping with calcium hydroxide. These are the first morphological and functional data derived from application of this protein directly on pulp exposure. 20 maxillary first molars from Wistar male mice were used, with 60 days of age, between 200 and 300 grams, which were divided in 4 groups (n=5): G1 and G3, controls, capped with calcium hydroxide in 7 and 30 days, respectively; G2 and G4, capped with sericin in 7 and 30 days, respectively. Circular cavities were prepared for pulp exposure, where capping materials were applied, being posteriorly restored with glass ionomer cement. At the end of the groups period, animals were euthanized and molars were histologically processed for analysis in light microscopy to evaluate presence of necrosis in pulp tissue, inflammatory cells infiltration and tertiary dentin formation. After 7 days, there was less necrosis and inflammatory cells infiltration in G1 when compared to G2 (p=0.007 and p=0.008, respectively). After 30 days, a sample of G3 induced tertiary dentin formation and G4 showed decrease in inflammation (p=0.041) compared to G2. Among the determined experiment conditions, it was concluded that sericin did not present to be viable to treatment as it did not induce tertiary dentin formation, although, its contact with pulp tissue has shown improve in inflammatory response during the treatment and new cells proliferation.